2009
DOI: 10.1177/1753193409347509
|View full text |Cite
|
Sign up to set email alerts
|

Epidermoid cysts in the hand

Abstract: This study details our series of epidermoid cysts in the hand, characterising the incidence, clinical characteristics and recurrence rate after marginal excision. A historical cohort of 101 epidermoid cysts that were excised from a soft tissue or intraosseous location in the hand over a 27 year period were reviewed. The incidence of epidermoid cysts, patient age, sex, occupation, anatomic location, history of trauma, treatment complications and cyst recurrence rate were noted. Key findings of the study were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 10 publications
1
39
0
2
Order By: Relevance
“…We think that the reason for this is; form of treatment is converted from marginal excision to intralesional excision by having intraoperative rupture, because the surrounding tissue is contaminated by the pathological cell planting via intralesional excision. [6] As a result of the data obtained from the present study, depending on the hypothesis that the skin on the cyst with/ without trauma history is defective to be predisposed to epidermoid cyst formation and possible defects on such site may allow transmission of epidermal formations into the dermis, we recommend removal of the cysts with cutaneous islets. Despite the current literature, we observed that intraoperative rupture is a reason for relapse of the cyst in the present study and concluded that this may be reduced by excision with cutaneous islet on the cyst.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…We think that the reason for this is; form of treatment is converted from marginal excision to intralesional excision by having intraoperative rupture, because the surrounding tissue is contaminated by the pathological cell planting via intralesional excision. [6] As a result of the data obtained from the present study, depending on the hypothesis that the skin on the cyst with/ without trauma history is defective to be predisposed to epidermoid cyst formation and possible defects on such site may allow transmission of epidermal formations into the dermis, we recommend removal of the cysts with cutaneous islets. Despite the current literature, we observed that intraoperative rupture is a reason for relapse of the cyst in the present study and concluded that this may be reduced by excision with cutaneous islet on the cyst.…”
Section: Discussionmentioning
confidence: 70%
“…[10] Epidermoid cysts of the hand are commonly observed on volar side of the hand and fingers and it is believed that cysts localized on the hand appear as a result of implantation of epidermal elements into dermis after a trauma. [6,11] Lincoski et al [6] found the incidence ratio of epidermoid cyst as 16% in their study where 623 masses were localized on the hand and forearm. Since we only evaluated cases that were diagnosed as epidermoid cyst histopathologically, we cannot provide such a ratio; however, we detected that 50% (n=60) of the cases were localized on the hand and forearm.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Dupuytren's nodules, ganglion cysts, and tendon sheath-induced tumors are the most common structures in palmar side of the hand [1,2]. Epidermoid inclusion cysts are frequently observed in hairy areas such as scalp, face, neck, and scrotum [3,4].…”
Section: Introductionmentioning
confidence: 99%